2010
DOI: 10.1016/j.childyouth.2010.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Do maltreated children who remain at home function better than those who are placed?

Abstract: The majority of children in the child welfare system remain with their maltreating parents, yet little is known about their level of functioning and whether they are in need of mental health intervention. The purpose of this study was to evaluate the mental health functioning of an ethnically diverse sample of 302 maltreated children and 151 non maltreated children ages 9-12 to see if there were differences between those who remained at home, those placed in kin care, nonrelative foster care or a comparison gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Concerns about the child's behavioural, cognitive, emotional and physical health have consistently been shown as important in substantiation and placement decisions (e.g., McConnell et al 2011;Mennen et al 2010;Tonmyr et al 2010a;Trocmé et al 2004). Among the variables we tested, only toxicology at birth showed an increased association with placement.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Concerns about the child's behavioural, cognitive, emotional and physical health have consistently been shown as important in substantiation and placement decisions (e.g., McConnell et al 2011;Mennen et al 2010;Tonmyr et al 2010a;Trocmé et al 2004). Among the variables we tested, only toxicology at birth showed an increased association with placement.…”
Section: Discussionmentioning
confidence: 92%
“…An earlier analysis of 9 to 12 year-olds found that maltreatment type did not influence placement decisions in Los Angeles (Mennen et al 2010). The authors suggested that the maltreatment form that triggered the initial investigation may not be indicative of the form of maltreatment that was identified following an investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Cohorts included the National Survey of Child and Adolescent Wellbeing (NSCAW, Berger et al ., 2009; Casanueva et al ., ; Cheng and Lo, ; Hurlburt et al ., ; Kolko et al ., ; Leslie et al ., , ; Raghavan et al ., ; Ringeisen et al ., ; Stacks et al ., ; Stahmer et al ., ; Traube et al ., ; Wall and Kohl, ) and the NSCAW‐II (Font and Maguire‐Jack, ; Fowler et al ., ; Horwitz et al ., ), a data‐set developed by Widom (DeGue and Spatz Widom, ; McMahon and Clay‐Warner, ; Widom, ), Swedish registry data (Berlin et al ., ; Vinnerljung et al ., , ), Runyan and Gould's (, ) historical cohort, a cohort used by Mennen et al . () and Negriff et al . () and five separate cohort studies (Baskin and Sommers, ; Doyle, ; Goodkind et al ., ; Lee, ; Pinto and Maia, ).…”
Section: Resultsmentioning
confidence: 99%
“…Attending to the needs of the mothers is vital to improve the outcome of the children in their care. We have previously found that the maltreated children who remain at home have the same rates of mental health problems as those in care and many meet clinical symptom levels (Mennen, Brensilver, & Trickett, 2010; Mennen & Trickett, 2007). Given the mutual interactive effect of parent and child mental health problems (Elgar, McGrath, Waschbusch, Stewart, & Curtis, 2004), it is unlikely that children's conditions will improve without parent treatment.…”
Section: Discussionmentioning
confidence: 99%